(3GdSMQ GdMdGd ef GHOGY GdLdGds - (3fGUQ GdOjf eMeO Hf bGfUhg Hf UGObs ((3CHh GdaVd eMeO Hf YHOGdhgGH GdCYQL GdSfehWi s)
(3ChdgG (B:s
(3hHYO abO SGdfi HYV GdENhGf ef GdCPcjGA GdaVdGA GdYjGf GdeKbajf Ydi GddZIhGdJUQja hdfMh hGdHOjY hGdeYGfi hGdHjGf Gf GNJUQ dg OjhGfi GdeSei HEHOGY QGdLdGd ai GdSMQ GdMdGd s
(3BNQgG (B:s
(3ef bUjOI eWdYgG SdGe Ydjce cdeG hbO GdhaO SdGe eMH ai MKGKJg GdhbO hBNQgG SdGe Ydjceč čč Ydjce ai cd hbJ hSGYg Ghda djS jNU dg YO s
(3GHOGY GdLdGdi gh OjhGf TYQg hgPG eNJUQI QJHg NeS ebOhGf hNeS GHhGHs
(3HChdgG Jdc HGdbSWfWjfjI SfI (B1092 (3g`R hQJgG eRNQaI hePgHI hYdjgG GSe GdcJGH heDdaI hHMhGTjgG JYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B148s
Keywords: (3GdCOHs